1992
DOI: 10.1021/j100181a064
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and thermodynamic aspects of the SDS-EHEC-water system

Abstract: The specific interaction between a strongly hydrophobic but still water-soluble cellulose derivative, ethyl(hydroxyethy1)cellulose (EHEC), and a low molecular weight anionic surfactant, sodium dodecyl sulfate (SDS), is studied in dilute solution without added neutral electrolyte by means of hydrodynamic (viscosity) and thermodynamic (dialysis equilibrium) measurements. The dialysis equilibrium shows strong adsorption of SDS at concentrations far below the normal cmc for SDS. The dialysis equilibrium is sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 0 publications
7
127
0
3
Order By: Relevance
“…34 In addition, the maximum viscosity at 4 × 10 -3 mol L -1 is also close to the value observed for SDS/ethyl(hydroxyethyl)cellulose systems independently of the polymer concentration. 1,14,35 The occurrence of the maximum viscosity above C 1 can be attributed to the formation of interchain polymersurfactant complexes. 1,3,36 The subsequent decrease in the viscosity with increasing SDS concentration indicates that the aggregate formation leads to a more compact polymer structure due to intrachain polymer-surfactant complexes.…”
Section: Resultsmentioning
confidence: 99%
“…34 In addition, the maximum viscosity at 4 × 10 -3 mol L -1 is also close to the value observed for SDS/ethyl(hydroxyethyl)cellulose systems independently of the polymer concentration. 1,14,35 The occurrence of the maximum viscosity above C 1 can be attributed to the formation of interchain polymersurfactant complexes. 1,3,36 The subsequent decrease in the viscosity with increasing SDS concentration indicates that the aggregate formation leads to a more compact polymer structure due to intrachain polymer-surfactant complexes.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the clue to the explanation for this unusual result is analogous to that proposed earlier by Holmberg et al to explain the primary step in the formation of polymer/surfactant complexes. 19 In the present systems the bound surfactant in the T 1 -T f region polymer and schiff-base are a "loose" aggregate which only binds a small amount of Br − counter ion. However the positive charge density at the surface of these bound aggregates are likely to attract Br − counter ions in such a way that the local concentration of Br − ions in the microenvironment of the complex is much higher than their bulk concentration.…”
Section: Resultsmentioning
confidence: 79%
“…Unfortunately we have not been able to observe any point at which the EMF data merge after binding in the present work and also in previous electrode studies on cationic surfactants. 14,19 We believe that part of this problem may be due to the electrode not responding ideally at higher surfactant concentrations. Certainly we have found that the high surfactant concentration response of the electrode is dependent on the origin of the modified poly vinyl chloride used for the membrane and also on high salt concentration.…”
Section: Resultsmentioning
confidence: 99%
“…These are very helpful for the specific targeting to tissues or cells. Synthetic polymers are utilized to get a broad and united picture of the interaction as this show a discrepancy in the nature and degree of substitution [35].…”
Section: Polymer-amphiphile Interactionsmentioning
confidence: 99%